Elevated levels of C-reactive protein and pig major acute phase protein in lame gestating sows - Jakobsen, Nadia; Larsen, Inge; Weber, Nicolai R.; Heegaard, Peter M. H.; Pedersen, Ken S. (Frontiers in Veterinary Science, 2025)
IntroductionLameness is a common clinical issue in gestating sows and a leading cause for early culling and antibiotic treatment. Diagnostic tools are limited, but acute acute phase proteins (APPs) could offer a fast and minimally invasive method for optimizing treatment. The aim of this study was to investigate whether APP level measurements can be used as a diagnostic tool, and to identify which major acute phase proteins are elevated in lame gestating sows.MethodsTo determine this, blood samples were collected from the jugular vein of 50 lame and 50 clinically healthy gestating sows from 12 conventional herds. The samples were analyzed for C-reactive protein (CRP), haptoglobin, serum amyloid A, and pig major acute phase protein (Pig-MAP) levels using sandwich ELISA.ResultsC-reactive protein and Pig-MAP were found to be significantly elevated in lame sows compared to clinically healthy sows (p < 0.05). The acute phase protein levels were 22.4 μg/ mL for CRP and 1.19 mg/mL for Pig-MAP in lame sows, compared to 14.7 μg/mL for CRP and 1.06 mg/mL for Pig-MAP in healthy sows.Acute phase protein levels were not associated with clinical signs of inflammation on the affected leg(s), and no differences were seen in hematology parameters between lame and healthy gestating sows.ConclusionIn this study, lameness was associated with an elevation in C-reactive protein and pig major acute phase protein.